Panel: "Community leadership and public leadership" - Asensio, M.; Sousa, M. (IIAS-EUROMENA Conference, ROME, 2022: "“Next Generation Governance and young global public administration: mobilizing people, skills, energies for a sustainable new normal”, 2022)
Description of the Panel: "Community leadership and public leadership" The spread of the COVID-19 pandemic has had to cope with constant changes that affect the public administration (Moon et al, 2020). During the pandemic, governments must respond to emergencies by organizing rapid responses and mobilizing resources. Confronted with dramatic uncertainty, which imposed rapid action, leaders need to nurture resilience. Community leadership and effective governance require capacities and capabilities for both agility and resilience. Public-sector capacity is typically defined as the set of skills, capabilities and resources necessary to perform policy functions, from the provision of public services to policy design and implementation (Drechsler and Kattel, 2020). Unfortunately, these are not only missing in reality, but they are also missing in the literature. The most comprehensive literature review of dynamic capabilities in the public sector to date shows that our existing frameworks focus on exogenous sources of dynamism. Similarly, strategy and leadership in public sector organizations tend to focus on the importance of individual leaders and teams in driving strategic initiatives. Thus, the capacities associated with the public sector tend to be narrow and focus on stability. To enrich the current understanding of the way resilient leadership unfolds to respond to shocks, this panel will address a reflection on leadership from different points of view involving the presence of young global public managers, the importance of gender and leadership, and community leaders' role in the public administration (Drolet, 2020; Ashikali, T., Groeneveld, S., & Kuipers, B. (2020). The panel seeks to answer the following question: what leadership role trends are relevant in public administration concerning resilience and the ability to adapt in times of crisis? How public sector organizations can ensure the effective pursuit of leadership by mobilizing people, skills, and energies for a sustainable new normal? References Ashikali, T., Groeneveld, S., & Kuipers, B. (2020). The Role of Inclusive Leadership in Supporting an Inclusive Climate in Diverse Public Sector Teams. Review of Public Personnel Administration, 41(3), 497–519. Boin, Arjen, and Paul ’t Hart. (2003). Public Leadership in Times of Crisis: Mission Impossible? Public Administration Review 63(5): 544–53. Drechsler, W. & Rainer Kattel (2020). Debate: The developed civil servant—providing agility and stability at the same time, Public Money & Management, DOI: 10.1080/09540962.2020.1729522 Drolet, C. A. (2020). Globalization and the challenges of public administration: governance, human resources management, leadership, ethics, e-governance and sustainability in the 21st century. International Review of Public Administration, 15. doi:10.1080/12294659.2020.1769325 Moon, M.J. (2020). Fighting COVID-19 with Agility, Transparency, and Participation: Wicked Policy Problems and New Governance Challenges. Public Administration Review, Vol. 80, Iss. 4, pp. 651–656 The American Society for Public Administration. DOI: 10.1111/puar.13214.